PROBLEMS OF ECONOMIC POLICY EFFECTIVENESS (Proceedings of the YSU C: Geological and Geographical Sciences, 2021)
The success or failure of national economy's development depends on effectiveness of economic policy. However, many countries record failures or low rates of economic development. It becomes necessary to clarify the reasons for the failure of economic policy and the factors affecting its effectiveness. The article highlights the factors affecting economic policy's effectiveness, its implementation and synergy with other subsystems. By our observations, the factors affecting the effectiveness of economic policy development are:– at the stage of theoretical justification: the complexity of the economic system, the multiplicity of economic decisions, the contradiction of approaches;– at the stage of institutional coordination: external geopolitical and geo-economic interests, internal political interests, target hypotheses. As a result of a lack of knowledge or pressure from stakeholders the theoretical justification of economic policy may not correspond to priorities of country's economic development. Even if economic policy is scientifically substantiated, it's implemented by political institutions and redesigned in favour of political efficiency. If political institutions are extractive and protect the interests of the elite, economic efficiency is sacrificed to private interests. Factors affecting the effectiveness of the implementation of economic policy: protection of property rights, impartiality of the judiciary, lack of corruption, bureaucracy, crime, political stability․ Without improving the business environment, economic policy is either ineffective or does not work at all. Factors affecting the effectiveness of systemic interaction (synergy) of economic policy with other subsystems that contributes to its development: development of infrastructures, education and science, environmental protection, etc. No less important is the interactions of these subsystems. Knowledge of the factors affecting the effectiveness of economic policy enables us to move from situational decisions to strategic and well-grounded decisions and, thereby, contribute to increasing the effectiveness of economic policy․
Keywords: economic policy; economic development; economic strategy; economy